Effects of benzene and its metabolites on global DNA methylation in human normal hepatic l02 cells. Issue 1 (23rd September 2011) - Hu, Junjie; Ma, Huimin; Zhang, Wenbing; Yu, Zhiqing; Sheng, Guoying; Fu, Jiamo
<x xml:space="preserve">Abstract</x> Benzene is an important industrial chemical that is also widely present in cigarette smoke, automobile exhaust, and gasoline. It is reported that benzene can cause hematopoietic disorders and has been recognized as a human carcinogen. However, the mechanisms by which it increases the risk of carcinogenesis are only partially understood. Aberrant DNA methylation is a major epigenetic mechanism associated with the toxicity of carcinogens. To understand the carcinogenic capacity of benzene, experiments were designed to investigate whether exposure to benzene and its metabolites would change the global DNA methylation status in human normal hepatic L02 cells and then to evaluate whether the changes would be induced by variation of DNA methyltransferase (DNMT) activity in HaeIII DNMT‐mediated methylation assay in vitro. Our results showed that hydroquinone and 1, 4‐benzoquinone could induce global DNA hypomethylation with statistically significant difference from control (p < 0.05), but no significant global DNA methylation changes were observed in L02 cells with benzene, phenol, and 1, 2, 4‐trihydroxybenzene exposure. Benzene metabolites could not influence HaeIII DNMT activity except that 1, 4‐benzoquinone shows significantly inhibiting effect on enzymatic methylation reaction at concentrations of 5 μM (p < 0.05). These results suggest that benzene metabolites, hydroquinone, and 1, 4‐benzoquinone can disrupt global DNA methylation, and the potential epigenetic mechanism by which that global DNA hypomethylation induced by 1, 4‐benzoquinone may work through the inhibiting effects of DNMT activity at 10 μM (p < 0.05). © 2011 Wiley Periodicals, Inc. Environ Toxicol 29: 108–116, 2014.